Medical and Behavioral Aspects of Adolescent Endometriosis: A Review of the Literature - Maria-Konstantina Liakopoulou; Ermioni Tsarna; Anna Eleftheriades; Angeliki Arapaki; Konstantina Toutoudaki; Panagiotis Christopoulos (MDPI AG, 2022)
The majority of young women will experience discomfort associated with menstrual cycles and miss out on education and social opportunities. Endometriosis, the presence of endometrial glands and stroma outside of uterus, is the most common cause of secondary dysmenorrhea and characterized by pain despite treatment with nonsteroidal anti-inflammatory drugs and hormonal agents. The true prevalence of adolescent endometriosis is not clear. Delay in diagnosis leads to persistent pain, affects quality of life, and potentially contributes to disease progression and subfertility. A laparoscopic diagnosis is the gold standard, but the surgical appearance may differ from adults, as endometriotic lesions are usually red or clear, making their identification a challenge for gynecologists who are unexperienced with endometriosis in adolescents. A personalized medical-surgical treatment is regarded as the most effective therapeutic strategy to achieve remission of symptoms, suppress disease progression, and protect future fertility. Studies have demonstrated how adolescent endometriosis negatively affects patients' quality of life and psychosocial functioning. Development of therapeutic interventions targeting psychosocial function and quality of life is imperative for adolescent patients.